Constitutional and legal regulation rights to information in the Republic оf Kazakhstan (Journal of actual problems of jurisprudence, 2021)
The article deals with the right to information as an important modern constitutional law that arose and was actualized under the influence of the information revolution. ХХ – beg. XXI century. It is noted that the «digital era» also affected the Kazakh society, in connection with which a new type of legal relations – information ones – took shape. The history of the origin and formation of the institution of the right to information in the national legislation of the Republic of Kazakhstan is traced. Modern scientific approaches and views on the nature and composition of the powers of this right are examined. The constitutional-legal regulation of the right to information in the Constitution of the Republic of Kazakhstan in 1993 and 1995 is analyzed. The right to receive information should be considered to clarify the issue raised in the article. The generally accepted understanding of this issue in the special scientific literature is not defined. At the moment, only the beginning of the formation of a scientific approach to the legal nature of the right to access information. The right to receive information in accordance with one of them is an exclusive right based on legal opportunities, access to “governmental information” of the public (information arising from the exercise of public authorities). As a result of the influence of the “digital age” at the transnational and national levels, global changes in human life have led to scientific and theoretical debates, as well as to a revision of the existing regulatory framework governing modern global processes. Key words: right to information, information society, right to information, constitutional legal regulation of the right to information.